2016
DOI: 10.1016/j.jmb.2016.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Shaping the Immune Landscape in Cancer by Galectin-Driven Regulatory Pathways

Abstract: Along with the discovery of tumor-driven inflammatory pathways, there has been a considerable progress over the past 10years in understanding the mechanisms leading to cancer immunosurveillance and immunoediting. Several regulatory pathways, typically involved in immune cell homeostasis, are co-opted by cancer cells to thwart the development of effective antitumor responses. These regulatory circuits include the engagement of inhibitory checkpoint pathways (CTLA-4, PD-1/PD-L1, LAG-3 and TIM-3), secretion of im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
72
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 153 publications
(104 reference statements)
2
72
0
1
Order By: Relevance
“…They contribute to many hallmarks of cancer, including sustained cell proliferation, inhibition of apoptosis, evasion of immune surveillance, promotion of angiogenesis, and induction of the metastatic process (37)(38)(39)(40). They do so by modulating the interactions between tumor, endothelial, stromal, and immune cells (37)(38)(39)(40)(41)(42). Yet, in spite of the wealth of information concerning the expression of different galectins during tumor progression (37), the molecular basis for their role in cancer growth and metastasis remains incompletely understood.…”
Section: B Gal-8 and Cancermentioning
confidence: 99%
“…They contribute to many hallmarks of cancer, including sustained cell proliferation, inhibition of apoptosis, evasion of immune surveillance, promotion of angiogenesis, and induction of the metastatic process (37)(38)(39)(40). They do so by modulating the interactions between tumor, endothelial, stromal, and immune cells (37)(38)(39)(40)(41)(42). Yet, in spite of the wealth of information concerning the expression of different galectins during tumor progression (37), the molecular basis for their role in cancer growth and metastasis remains incompletely understood.…”
Section: B Gal-8 and Cancermentioning
confidence: 99%
“…The article by Rabinovich and Conejo-Garcia [16] explores how different galectins play roles in promoting inflammation, immunosuppression, and angiogenesis in cancer progression. They further suggest that understanding the roles of galectin-driven pathways that influence tumor progression will likely lead to the development of new therapeutics that would be applicable to a wide variety of different cancers.…”
Section: Myriad Roles Of Glycans In Biologymentioning
confidence: 99%
“…Developing studies in tumor immunology have identified gamma-delta (γδ) T cells as functioning under a suppressive program in order to dampen anti-tumor immunity and facilitate malignant progression. γδ T cells outnumber conventional αβ CD4+ Tregs in many solid tumors such as breast and ovarian cancers, yet they remain underinvestigated (Rabinovich, Conejo-Garcia 2016). Therefore, extending our understanding of the mechanistic properties driving the suppressive nature of such cells may lead to enhanced prognostic and therapeutic benefit.…”
Section: Introductionmentioning
confidence: 99%